การศึกษาความเป็นไปได้ในการลงทุนธุรกิจที่พำนักระยะยาวสำหรับผู้เกษียณอายุชาวญี่ปุ่นในจังหวัดเชียงใหม่ - อรรถวุฒิ เรืองตรานนท์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The independent study has purposed to study a feasibility on the investment of a long stay for retired Japanese in Chiang Mai Province by using the approach of project feasibility analysis which comprise of Marketing, Technique, Environment, Economy, Monetary Planning and Law and Social. The study has collected data by interview the 4 elderly long stay entrepreneurs and do questionnaires from 135 samples which get 117 returns, return rate is 86.67 percent. The result of the study have been concluded by each comprisals as Marketing, Japanese visit Chiang Mai in long period and most of them like to travel in Chiang Mai because of the satisfaction in the circumstance and atmosphere. Besides the market of long stay for elderly is interested from the investor but cannot enter to this business easily because of the high in investment that effect to the number of competitive in the market is less. While the long stay for retired Japanese responses their customer requirement at most. Technique, the long stay for retired Japanese is located on Chotana Road Chang Puek District Muang Chiang Mai Chiang Mai Province with the 22 Rai land. The buildings and constructions are in contemporary style. The long stay for retired Japanese has operated as a juristic person, company limited and operated and managed in term of the hotel and resort. Environment, the long stay for retired Japanese has designed to be harmonized with the surrounding circumstance and to have the positive understanding with community the project will do cooperated with all community activity and community development. Economic, the long stay for retired Japanese has invested in amount totally 25 Million Baht from shareholder. The project period is 10 years. Furthermore, overall income projection is 108,099,640.00 Baht. Expense projection along the project is approximately 82,531,218.03 Baht. Monetary planning, the appraisal of the long stay for retired Japanese feasibility has discount rate at 6 percent that make the project Net Present Value (NPV) 2,066,096.76 Baht and Internal Rate of Return (IRR) of the project in the percentage of 7.54 that is higher than the indicate IRR which is percentage of 6. In addition, the long stay for retired Japanese has payback period in 7 years 4 months and 14 days. Law and Social, the long stay for retired Japanese is related with the many government sectors and regulations such as Department of Business Development, Revenue Department, Immigration and Department of Local Administration. With the study result, the study conclude that the long stay for retired Japanese have possibility on investment.